Relationship between 129I and 127I contents in bovine thyroid glands from Argentina - Negri, Agustin Eduardo (2013)
129I/127I ratios and iodine concentrations in bovine thyroids stemming from Argentina were determined by accelerator mass spectrometry (AMS) and gas chromatography (GC), respectively. From these measurements, a relationship of the 129I/127I ratio with iodine content in the gland was obtained. A weak correlation between the two isotopes was found, suggesting that 129I re-emission from the ocean is not the only process for the 129I deposition in Argentina. Moreover, contributions to the total 129I inventory in the Southern hemisphere from both natural and anthropogenic sources were theoretically studied. Surface compartments present similar contribution from natural sources and nuclear explosions fallout.